Self-Care in the Elderly with Hypertension - Suradi Efendi; Nour Sriyanah; Satriana Dardi; Hilmiah Hilmiah; Agriyati Wirasti; Megawati Megawati (Global Health Science Group, 2022)
The Elderly is an individual in the final stage of development with several characteristics, such as having various needs and problems, both from bio-psychosocial and spiritual needs. Self-care is one of the basic needs in the process of every human life. Self-care in the elderly will change due to aging, which decreases independence. This study aimed to find out the overview of Self-Care in the Elderly with Hypertension in the Work Area of UPT Puskesmas Usa. This study used a survey design, and the number of samples was 110 elderly with hypertension. This study used a non-probability sampling technique. The descriptive statistical test showed that self-care in the elderly with hypertension in the work area of UPT Puskesmas Usa was in the most category with poor self-care. Therefore, it is necessary to increase the guidance and health education for the elderly regarding self-care management in hypertension.